Enhanced secondary pollution offset reduction of primary emissions during COVID-19 lockdown in China. Issue 2 (18th June 2020) - Huang, Xin; Ding, Aijun; Gao, Jian; Zheng, Bo; Zhou, Derong; Qi, Ximeng; Tang, Rong; Wang, Jiaping; Ren, Chuanhua; Nie, Wei; Chi, Xuguang; Xu, Zheng; et al.
Abstract: To control the spread of the 2019 novel coronavirus (COVID-19), China imposed nationwide restrictions on the movement of its population (lockdown) after the Chinese New Year of 2020, leading to large reductions in economic activities and associated emissions. Despite such large decreases in primary pollution, there were nonetheless several periods of heavy haze pollution in eastern China, raising questions about the well-established relationship between human activities and air quality. Here, using comprehensive measurements and modeling, we show that the haze during the COVID lockdown was driven by enhancements of secondary pollution. In particular, large decreases in NOx emissions from transportation increased ozone and nighttime NO3 radical formation, and these increases in atmospheric oxidizing capacity in turn facilitated the formation of secondary particulate matter. Our results, afforded by the tragic natural experiment of the COVID-19 pandemic, indicate that haze mitigation depends upon a coordinated and balanced strategy for controlling multiple pollutants.